(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Phytomyza trolliicaulis, a new species of Agromyzidae, stem miner of Trollius europaeus, is described. The male genitalia place trolliicaulis in the "opaca" group, living on Ranuncolaceae plants.